(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
Background: Stress impacts physical and psychological well-being, affecting mental and physical health. Job satisfaction, influenced by work conditions and relationships, is crucial for productivity and workplace success. In teaching, occupational stress is a significant concern, with workload, pay, and burnout affecting job satisfaction and educational outcomes. Balancing stress and job satisfaction is essential for improving teacher well-being, motivation, and educational quality. Methods: A web-based quantitative study conducted in Nepal from August to November 2024 compared job satisfaction and stress levels among teachers using a self-administered questionnaire distributed via Google Forms. Data were collected from 323 school teachers aged 20 to 59 teaching levels from Early Childhood Development (ECD) to Grade 12 through a snowball sampling method. Results: ECD teachers have significantly lower job satisfaction levels (P = 0.036), while all other teachers are less satisfied than permanent teachers (P < 0.001). Teachers with over 20 years of experience are more satisfied (P = 0.008), while those who have only passed the SLC exam are less satisfied (P < 0.001). Teachers aged over 45 experience significantly lower stress levels (P < 0.001). Teachers at the 10+2 quota (P = 0.003), secondary level (P < 0.001), and lower secondary level (P = 0.035) reported lower stress levels, while ECD teachers exhibited higher stress levels (P = 0.002). Teachers belonging to the Muslim, Christian, or Kirat religions reported higher stress levels (P = 0.028), and unmarried teachers also experienced higher stress levels (P < 0.001). Conclusion: Policy reforms should prioritize fair salaries, equitable promotions, and improved workload management to support high-stress groups and enhance the teaching environment.